2021
DOI: 10.3390/nu13082612
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Clinical Evidence of the Effectiveness of Riboflavin on Migraines

Abstract: Riboflavin, a water-soluble member of the B-vitamin family, plays a vital role in producing energy in mitochondria and reducing inflammation and oxidative stress. Migraine pathogenesis includes neuroinflammation, oxidative stress, and mitochondrial dysfunction. Therefore, riboflavin is increasingly being recognized for its preventive effects on migraines. However, there is no concrete evidence supporting its use because the link between riboflavin and migraines and the underlying mechanisms remains obscure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Our ndings on OBS and migraine were reliable and similar to most previous studies.The dietary components of OBS encompass numerous ingredients, many of which have been substantiated in prior studies for their antioxidant effects.A research demonstrated that increasing the intake of ber-rich foods can prevent severe headaches or migraines [31].Ribo avin plays a crucial role in preventing various health conditions, including migraines [32,33].Ribo avin may exert neuroprotective effects through its clinically bene cial anti-in ammatory and antioxidant stress properties. A German randomized, placebo-controlled, double-blind, multicenter trial has demonstrated that intervention with a patented supplement containing magnesium, ribo avin, and Q10 signi cantly reduces the frequency of migraine attacks, migraine symptoms, and disease burden in individuals suffering from migraine attacks compared to a placebo [34].Niacin is an essential coenzyme in mitochondrial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings on OBS and migraine were reliable and similar to most previous studies.The dietary components of OBS encompass numerous ingredients, many of which have been substantiated in prior studies for their antioxidant effects.A research demonstrated that increasing the intake of ber-rich foods can prevent severe headaches or migraines [31].Ribo avin plays a crucial role in preventing various health conditions, including migraines [32,33].Ribo avin may exert neuroprotective effects through its clinically bene cial anti-in ammatory and antioxidant stress properties. A German randomized, placebo-controlled, double-blind, multicenter trial has demonstrated that intervention with a patented supplement containing magnesium, ribo avin, and Q10 signi cantly reduces the frequency of migraine attacks, migraine symptoms, and disease burden in individuals suffering from migraine attacks compared to a placebo [34].Niacin is an essential coenzyme in mitochondrial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies proved that riboflavin as a single component was effective in migraine prophylaxis and treatment. 19,[21][22][23][35][36][37] A randomized controlled trial by Schoenen et al 21 compared oral riboflavin (400 mg/day) and placebo among 55 patients with migraine of 3 months duration, and revealed that riboflavin was superior in decreasing headache days and frequency with minor adverse effects (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…NQO1 is increased by oxidative stress as a part of the Nrf2 battery of stress response genes and the elevation of NQO1 associated with AD pathology is commonly viewed as a neuroprotective response to the oxidative stress that accompanies AD [ 6–8 ]. Interestingly, riboflavin is a neuroprotective agent known to limit oxidative stress, mitochondrial dysfunction, and neuroinflammation [ 43 , 44 ] and to slow the rate of cognitive decline in the elderly [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%